Anti-Aging Effect of the Stromal Vascular Fraction/Adipose-Derived Stem Cells in a Mouse Model of Skin Aging Induced by UVB Irradiation - Wang, Jingru; Chen, Yuanwen; He, Jia; Li, Guiqiang; Chen, Xiaodong; Liu, Hongwei (Frontiers in Surgery, 2022)
Adipose-derived stem cells(ADSCs) have been used for anti-photo-aging. But the purification of ADSCs requires in vitro amplification and culture, there is considerable risk of direct treatment for patients. Stromal vascular fraction(SVF) is a biologically and clinically interesting heterogeneous cell population contains ADSCs. There are few reports on anti-aging effects of SVF in photo-aging skin.The present study investigated the anti-aging effect of stromal vascular fraction (SVF) and adipose-derived stem cells (ADSCs) injection in photo-aging skin. The relationship between the dosage of injection and effect was also discussed. .Thirty healthy, 6-week-old, nude rats were randomly divided into the control and experimental groups. The experimental group needing ultraviolet B (UVB) irradiation five days per week, and a duration of 8 weeks. According to different dose regimens of SVF and ADSCs, experiment rats were randomly grouped as the model control group, low-dose (LD) treatment group, middle-dose (MD) treatment group and high-dose (HD) treatment group. At 7 and 28 days post-treatment, specimens were harvested for histological and immunohistochemical analysis.We found that certain concentrations of cells(MD and HD groups) could improve the texture of photoaged skin. Changes in the epidermal cell layer were clearly observed after 7 days of treatment. The epidermal layer becomes thinner and more tender.After 28 days of treatment, the dermal tissue was thickened and the collagen content and proportion were improved. All these indicators showed no significant difference between the same dosages in the two treatment groups. Our results demonstrate that SVF may have anti-aging potential in photo-aging skin and the ADSCs play an important role in SVF. SVF maybe a potential agent for photo-anging skin and the most effective dose of SVF was 106 cells /100μl/injection point. The proper injection interval may be 1.5cm.